Spin liquid and quantum phase transition without symmetry breaking in a frustrated three-dimensional Ising model - Roechner, Julia; Balents, Leon; Schmidt, Kai Phillip (Physical Review B, 2016)
We show that the highly frustrated transverse-field Ising model on the three-dimensional pyrochlore lattice realizes a first-order phase transition without symmetry breaking between the low-field Coulomb quantum spin liquid and the high-field polarized phase. The quantum phase transition is located quantitatively by comparing low-and high-field series expansions. Furthermore, the intriguing properties of the elementary excitations in the polarized phase are investigated. We argue that this model can be achieved experimentally by applying mechanical strain to a classical spin-ice material composed of non-Kramers spins such as Ho2Ti2O7. Taken together with our results, this provides an experimental platform to study quantum spin liquid physics.